Multifunctional nanomaterials composed entirely of active pharmaceutical ingredients for synergistically enhanced antitumor and antibacterial effects - An, Qi; Wang, Dongmei; Huang, Liang; Chen, Xiangyu; Wang, Chuan (Frontiers in Pharmacology, 2024)
The development of multifunctional nanomaterials has emerged as a promising strategy to address both cancer and bacterial infections. However, achieving dual therapeutic effects for cancer and bacterial treatment within a single system remains a challenge. Here, we developed multifunctional nanoparticles (ECI-NPs) through oxidative coupling reactions involving Epigallocatechin gallate (EGCG) oligomers, Curcumin (CUR), and Indocyanine Green (ICG). This nanomaterial enhances the photodynamic and photothermal effects of CUR and ICG, improving drug solubility and stability while promoting synergistic therapeutic outcomes. Physicochemical characterization of ECI-NPs demonstrated favorable stability, optimal particle size, high drug loading capacity, and controlled drug release profiles. Cellular studies revealed enhanced uptake and superior phototoxicity in melanoma cells when treated with ECI-NPs compared to free drugs. Additionally, the nanomaterial exhibited greater anticancer activity and potent antibacterial effects against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), surpassing the efficacy of individual components. The polyphenol-based nano-integrated platform presented in this study not only addresses the inherent limitations of the active pharmaceutical ingredients (APIs) but also demonstrates multiple synergistic functionalities. This approach holds great promise for broader biomedical applications, potentially offering innovative solutions for diverse therapeutic challenges.